2020
DOI: 10.1039/c8np00027a
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing diverse transcriptional regulators for natural product discovery in fungi

Abstract: This review covers diverse transcriptional regulators for the activation of secondary metabolism and novel natural product discovery in fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 76 publications
0
86
0
Order By: Relevance
“…Molds species from genera Aspergillus , Fusarium and Penicillium predominantly produce these bioactive secondary metabolites (SMs) (Keller, ). A survey showed that more than 1,500 compounds have been isolated from molds, and more than half of these compounds exhibited antimicrobial and/or antitumor activity (Lyu, Liu, Keller & Yin, ). This suggests that molds harbor an enormous secondary metabolome with potential applications for drug discovery (Schueffler & Anke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Molds species from genera Aspergillus , Fusarium and Penicillium predominantly produce these bioactive secondary metabolites (SMs) (Keller, ). A survey showed that more than 1,500 compounds have been isolated from molds, and more than half of these compounds exhibited antimicrobial and/or antitumor activity (Lyu, Liu, Keller & Yin, ). This suggests that molds harbor an enormous secondary metabolome with potential applications for drug discovery (Schueffler & Anke, ).…”
Section: Introductionmentioning
confidence: 99%
“…In working with the discovery of natural products, several research approaches have been reported to be involved in both secondary metabolism and fungal development [ 50 , 51 ]. It is urgent to find new approaches to distinguish new products from the known compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These sources can be either complex mixtures extracted from raw materials or single compounds. 2,3 Among the well-known medicinal fungi, Ganoderma lucidum (Curtis) P. Karst. and other species of Ganoderma showed greater advantages than other chemical drugs.…”
Section: Introductionmentioning
confidence: 99%